2017
DOI: 10.1016/j.cognition.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Representing composed meanings through temporal binding

Abstract: A key feature of human thought and language is compositionality, the ability to bind pre-existing concepts and word meanings together in order to express new ideas. Here we ask how newly composed complex concepts are mentally represented and matched to the outside world, by testing whether it is harder to verify if a picture matches the meaning of a phrase, like big pink tree, than the meaning of a single word, like tree. Five sentence-picture verification experiments provide evidence that, in fact, the meanin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Future work is clearly needed to develop the scope of these computational/cognitive models, In particular, work is needed to reveal how the meanings of multiple consecutive words can be simultaneously represented within the same network, most likely by allowing the semantic features of each word to remain separately bound to its corresponding phonological/orthographic features (Rabagliati, Doumas, & Bemis, 2017).…”
Section: Distributed Representations Of Word Meaningsmentioning
confidence: 99%
“…Future work is clearly needed to develop the scope of these computational/cognitive models, In particular, work is needed to reveal how the meanings of multiple consecutive words can be simultaneously represented within the same network, most likely by allowing the semantic features of each word to remain separately bound to its corresponding phonological/orthographic features (Rabagliati, Doumas, & Bemis, 2017).…”
Section: Distributed Representations Of Word Meaningsmentioning
confidence: 99%
“…Rather than rehash this proposal, we wish to address the issue of "scope" in phrase building, i.e., how some lexical items in a phrase can combine before others. While this issue has received considerable attention in the literature, Rabagliati et al (2017) provides insight of particular importance. Rabagliati et al (2017) used a behavioral experiment showing reaction time differences for processing different types of one-, two-, and three-word phrases with different scope interpretations.…”
Section: Combinatorial Processing In Linguistic Representations and B...mentioning
confidence: 99%
“…While this issue has received considerable attention in the literature, Rabagliati et al (2017) provides insight of particular importance. Rabagliati et al (2017) used a behavioral experiment showing reaction time differences for processing different types of one-, two-, and three-word phrases with different scope interpretations. Their results suggested that some types of three-word phrases are processed as quickly as two-word phrases, but more importantly, the time required to process a three-word phrase was related to its complexity and scopal interpretation.…”
Section: Combinatorial Processing In Linguistic Representations and B...mentioning
confidence: 99%
“…The model is an integration and augmentation of the LISA model of analogical reasoning (Hummel & Holyoak, 1997, 2003; Knowlton et al, 2012) and the DORA model of relational learning and cognitive development (Doumas & Martin, 2018; Doumas et al, 2008). LISA and DORA account for over 100 major findings in human perception and cognition, spanning at least seven domains: (a) shape perception and object recognition (Doumas & Hummel, 2010; Hummel, 2001; Hummel & Biederman, 1992); (b) relational thinking (Choplin & Hummel, 2002; Hummel & Holyoak, 1997, 2003; Hummel et al, 2014; Krawczyk et al, 2004, 2005; Kroger et al, 2004; Kubose et al, 2002; Taylor & Hummel, 2009), (c) relation learning (Doumas & Hummel, 2012; Doumas et al, 2008; Jung & Hummel, 2015a, 2015b; Livins et al, 2015, 2016), (d) cognitive development (Doumas et al, 2008; Licato et al, 2012; Lim et al, 2013; Sandhofer & Doumas, 2008), (e) language processing (Doumas & Martin, 2018; Martin & Doumas, 2017, 2020; Rabagliati et al, 2017), (f) cognitive aging (Viskontas et al, 2004), and (g) decline due to dementia, stress, and brain damage (Morrison et al, 2004, 2011). Accordingly, we view these systems as a promising starting point for an account of human-level cross-domain generalization.…”
Section: Relational Representations and Generalizationmentioning
confidence: 99%